TREATMENT OF A HIGH STRENGTH ACIDIC INDUSTRIAL CHEMICAL WASTEWATER USING EXPANDED BED ADSORBER (مجلة الهندسة, 2011)
Treatment of a high strength acidic industrial wastewater was attempted by activated carbonadsorption to evaluate the feasibility of yielding effluents of reusable qualities. The experimentalmethods which were employed in this investigation included batch and column studies. Theformer was used to evaluate the rate and equilibrium of carbon adsorption, while the latter wasused to determine treatment efficiencies and performance characteristics. Fixed bed and expandedbed adsorbers were constructed in the column studies. In this study, the adsorption behavior of acetic acid onto activated carbon was examined as a function of the concentration of the adsorbate, contact time and adsorbent dosage. The adsorption data was modeled with Freundlich and Langmuir adsorption isotherms.The amount of acetic acid adsorbed increased with the decrease in initial concentration of acetic acid and increased with the increase in contact time and adsorbent dose. The effects of variousimportant and influencing parameters such as flow rate, bed height, inlet adsorbate concentrationon breakthrough curve are studied in details in the column studies.